Mental Health, Emotional Relations and the Pandemic (Revista Iberoamericana de Bioética, 2023)
The context of the pandemic brought back the basic helplessness of the subject, resuming the concept stated by Freud in Civilization and its Discontents. The Austrian psychoanalyst refers to the real anguish whose consequence is traumatic. Moreover, the psychic mark of masochism is also reactivated by the fantasy of attributing suffering, which becomes almost a social imperative. It is evident that if in this context the subject still believes in a kind of appeal to the Other—through care and security—, the vulnerability and absence of this instance of protection lead the individual to the subjective condition of discouragement and, consequently, to a feeling of fragmentation and deconstruction (even deeper than that arising from post-modernity).
Keywords: affections; pandemic; technology; education; employment